Left knee septic monoarthritis in a pediatric patient due to shewanella putrefaciens: case report and literature review - Nathalie Yepes Madrid; Luis Fernando Mejia; José Fernando Gomez Urrego (BMC, 2024)
Abstract Background Shewanella putrefaciens is a gram-negative, nonfermenting, oxidase-positive, hydrogen sulfide-producing bacillus and a halophilic bacterium, known for causing unusual infections in humans and often regarded as an opportunistic pathogen. Its diverse symptoms have a significant impact on human health, with 260 documented disorders reported in the literature over the last 40 years, highlighting its potential danger. Case presentation We present the case of a previously healthy 15-year-old male patient who sustained a self-inflicted sharp-object injury while working in the field, resulting in secondary septic monoarthritis due to Shewanella putrefaciens. Conclusions This case highlights the bacteriological and clinical characteristics, as well as the antibiogram, of Shewanella spp. Given the recent increase in notifications of Shewanella infections, predominantly by S. algae and S. putrefaciens, it is essential to consider these pathogens in patients with a history of contact with bodies of water. Special attention must be paid to their resistance patterns in patient management to prevent the development of intrinsic antimicrobial resistance.